Study of Microflora in Patients with Benign Vascular Tumors of the Nasal Cavity (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article presents analytical studies of the microflora of 35 patients aged 18 to 65 years with inflammatory diseases of the nasal cavity and paranasal sinuses with benign vascular tumors of the nasal cavity. In patients with inflammatory diseases of the nasal cavity and paranasal sinuses with benign vascular tumors of the nasal cavity, the composition of the microflora differs from primary inflammatory diseases of the nasal cavity and paranasal sinuses: the degree of seeding of anaerobes, fungi and associations of microorganisms increases as the tumor grows and spreads.